Pre-sliding technique to improve femoral neck system against the shortening: a retrospective cohort study - Dongze Lin; Yaqian Liang; Peisheng Chen; Shunze Zheng; Fengfei Lin (BMC Musculoskeletal Disorders, 2024)
Abstract Objective To investigate the efficacy of using pre-sliding technique to prevent postoperative shortening of displaced femoral neck fracture fixed with femoral neck system (FNS). Methods Retrospective analysis of 110 cases of displaced femoral neck fracture treated with femoral neck system from September 2019 to November 2022 in our center, which were divided into 56 cases in the pre-sliding group and 54 cases in the traditional group. The baseline data such as gender, age, side, mechanism of injury, fracture type, operation time, intraoperative bleeding were recorded and compared between the two groups, and the quality of fracture reduction, shortening distance, Tip Apex Distance (TAD), union time, Harris score of the hip were also compared between the two groups. Results The TAD value of the pre-sliding group was smaller than that of the traditional group, and the difference was statistically significant (P < 0.001). The shortening distance in both groups on postoperative day 1 was smaller in the pre-sliding group than in the traditional group, but the difference was not statistically significant (P = 0.07), and the shortening distance was smaller than in the traditional group at 1, 3, 6, and 12 months postoperatively, and the difference was statistically significant (all P < 0.001). Of the 110 cases, 34 (30.9%) had moderate or severe shortening, of which 24 (44.4%) were in the traditional group and 10 (17.9%) in the pre-sliding group, and the difference was statistically significant (P < 0.001), and the Harris score at 1 year, which was higher in the pre-sliding group than in the traditional group, and the difference between the two groups was statistically significant (P < 0.001). There was no statistically significant difference in the comparison of baseline data such as gender, age, side, mechanism of injury, fracture type, operation time, intraoperative bleeding, and quality of reduction between the two groups (all P > 0.05), and no statistically significant difference in fracture healing time between the two groups (P = 0.113). Conclusion The use of the pre-sliding technique of displaced femoral neck fracture fixed with FNS reduces the incidence of moderate and severe shortening, improves the postoperative TAD value, and improves the hip function scores, with a satisfactory midterm efficacy.